Defining pharmacy and its practice: a conceptual model for an international audience - Scahill SL; Atif M; Babar ZU (Dove Medical Press, 2017)
SL Scahill,1 M Atif,2 ZU Babar3,4 1School of Management, Massey Business School, Massey University, Albany, Auckland, New Zealand; 2Pharmacy School, The Islamia University of Bahawalpur, Bahawalpur, Pakistan; 3School of Pharmacy, University of Huddersfield, Huddersfield, England, UK; 4School of Pharmacy, Faculty of Medical and Health Sciences, University of Auckland, Auckland, New Zealand Background: There is much fragmentation and little consensus in the use of descriptors for the different disciplines that make up the pharmacy sector. Globalization, reprofessionalization and the influx of other disciplines means there is a requirement for a greater degree of standardization. This has not been well addressed in the pharmacy practice research and education literature. Objectives: To identify and define the various subdisciplines of the pharmacy sector and integrate them into an internationally relevant conceptual model based on narrative synthesis of the literature. Methods: A literature review was undertaken to understand the fragmentation in dialogue surrounding definitions relating to concepts and practices in the context of the pharmacy sector. From a synthesis of this literature, the need for this model was justified. Key assumptions of the model were identified, and an organic process of development took place with the three authors engaging in a process of sense-making to theorize the model. Results: The model is “fit for purpose” across multiple countries and includes two components making up the umbrella term “pharmaceutical practice”. The first component is the four conceptual dimensions, which outline the disciplines including social and administrative sciences, community pharmacy, clinical pharmacy and pharmaceutical sciences. The second component of the model describes the “acts of practice”: teaching, research and professional advocacy; service and academic enterprise. Conclusions: This model aims to expose issues relating to defining pharmacy and its practice and to create dialogue. No model is perfect, but there are implications for what is posited in the areas of policy, education and practice and future research. The main point is the need for increased clarity, or at least beginning the discussion to increase the clarity of definition and consistency of meaning in-and-across the pharmacy sector locally, nationally and internationally. Keywords: defining pharmacy, global standardization, conceptual model, normative practices